WISATA KULINER SEBAGAI FENOMENA SOSIAL DAN KEKUATAN PERTUMBUHAN EKONOMI (Sebuah Studi Market) - hernawati retno wiratih (FIRM Journal of Management Studies, 2020)
Humans are unique creatures (Descartes, 1596-1650) humans are creatures who think (cogito); doubts about its existence the cogito ergo sum are answered which is building a relationship with their environment to develop themselves as human beingsm, wherever men have lived together there has been some group interest in food, traveling, and pleasure. This interest as group grows becomes more complex, and places in charged with the chance and challenge of feeding and offering is created. Human capital is not only a factor in economic growth, but also an effect of it or of developments generated by economic growth. The process of economic growth can explain much of the observed variation in the structure distribution among culinary foods as a social phenomenon. The global spread culinary industries produced benefit development of well-being in many areas. The contribution of culinary to economic well-being depends on the quality and revenues of the culinary that offer. The trend of  world community todays there is an interest increase of most of people, with their own reasons, they like to spend their time to the food court even a while. Due to the result of research shows that with 180 respondents from any reasons we try to study (ages of group of respondents, gender, education, occupation, the living area, their related Activities Culinary for. Lunch and or dining out is growing form of half of informal form and leisure where meals are consumed not out of necessity but also important sustainable positioning in ever more complex for pleasure and to build a relationships, the occasion are part of the leisure experiences as much as the food itself as social-belonging, esteem, and self-actualization (Hierarchy of Needs, Maslow, 1954), and event cultural object. In Sen’s capabilities approach which holds a person’s capability to have various functioning vectors and to enjoy the corresponding “well-being achievements” to the best indicator of welfare (Sen, 1985) means that culinary as social phenomenon growth amplifies the positive impacts of rotation economic and  market production at the same time welfare too. Key Words: Culinary, Leisure and Esteem, Self-Actualization, Growth Economic.